PENDAPATAN DAN KESEJAHTERAAN ANGGOTA KSP TANI MAKMUR KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Aldino Ahmad RES; Sudarma Widjaya; Umi Kalsum (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aimed to analyze cassava farming income received by members, the cooperative economic benefits received by members, revenue structure of farm household of KSP Tani Makmur members, and the level of welfare of members of KSP Tani Makmur.  This research was conducted in KSP Tani Makmur, Natar Sub-district South Lampung District, in which total members were 32 cassava farmers.  The data analysis was analysis of income, cooperative economic benefit analysis, analysis of household income, and analysis of the level of well-being according to BPS 2007. The result showed that the income of cassava farmers was on high level category with the highest contribution from cassava on farming.  Based on average income per capita, the income of farmers was already above the poverty line.  The economic advantages of indirect cooperative which was received by members still relatively low.  While the direct economic advantage in form of fertilizers loans becoming an active member motivation in cooperative. The revenue structure of cassava farmer obtained from various sources.  Those were cassava, yard, livestock, farm workers, trader, head of villagers, and cooperative. The level of farmers’ welfare based on BPS method in 2007, we got the result that all the farmer members fit into the category of being wellfare. Key words: cooperation, household, income, welfare